IDDF2020-ABS-0014 Comparison of the efficacy of povidone-iodine and normal saline wash in preventing surgical site infections in laparotomy wounds-randomized controlled trial. (18th November 2020) - HG, Vinay; Reddy, Ramesh
Abstract : Background: Povidine-Iodine has been utilized as a broad-spectrum antiseptic irrigation in the wound management processes for many years. However, some recent studies showed that the infection rate in laparotomy wounds decreases more by using normal saline. The study aims to examine the decreasing infection rate in laparotomy wounds by comparing the effectiveness and safety of povidine-iodine solution with normal saline. Methods: The patients undergoing elective laparotomies were included and randomly assigned to 2 groups. In the first group(90), incision wounds were flushed with 5% povidine-iodine solution. In the second group(90), incisions were flushed with 0.9% normal saline solution. By comparing the infection rates of the wound, outcomes were measured between the two groups. Results: Surgical site infections were seen in 16 of 180(12.5%) patients in povidine-iodine versus 7 in normal saline groups. The difference in the infection rates in the two studied groups(p = 0.6) has no statistical significance. Conclusions: The infection rate in laparotomy wounds did not increase or decrease when the wound was irrigated with 5% povidone-iodine solution or with 0.9% saline solution.